Quantitative and qualitative assessment of a pituitary neuroendocrine tumor’s T2-signal intensity in acromegaly – a call for unification - Godlewska-Nowak, Magdalena; Grochowska, Anna; Zieliński, Grzegorz; Bogusławska, Anna; Adamek, Dariusz; Maksymowicz, Maria; Hubalewska-Dydejczyk, Alicja; Gilis-Januszewska, Aleksandra (Frontiers in Endocrinology, 2024)
Introduction T2-signal intensity (SI) of somatotroph Pituitary Neuroendocrine Tumors (sPitNET) is associated with treatment response and granulation pattern. Our aim was to evaluate SI assessment methods and their clinical implications, including responsiveness to preoperative first-generation somatostatin analogues (SSA). Methods This single-center, observational study included unselected, consecutive patients with newly diagnosed acromegaly. Out of 109 treatment-naïve patients, 69 were eligible. The qualitative Visual Method involved visual comparison of the sPitNET with the temporal gray matter. The Three Tissue Method compared the quantified SI of the sPitNET, temporal white, and gray matter. The Signal Intensity Ratio of the sPitNET vs. Gray Matter (GM-SIR) was calculated. Tumors were divided into three groups: hyperintense (HYPER), isointense (ISO), hypointense (HYPO) according to the Visual Method, Three Tissue Method and GM-SIR. These groups were compared in terms of demographic, radiological and biochemical features. The SI assessment methods were investigated for their ability to predict preoperative SSA responsiveness. Results SI assessment methods classified SI type correspondingly in 58-73.9% of cases. ISO constituted 39-49% of the analyzed sPitNETs. All methods identified significant differences in tumor volume between SI groups, with HYPO being more biochemically active per tumor volume unit. According to the Three Tissue Method, patients with ISO had the youngest age at diagnosis and onset. According to the Visual Method, ISO had lower chance of achieving IGF1 normalization compared to HYPO (Odds Ratio (OR) 0.089, Confidence Interval (CI) 0.015-0.538, p= 0.008),), with no differences between HYPER and HYPO. Only Visual Method predicted the IGF1 normalization after SSA. HYPER and ISO sPitNETs were classified in electron microscopy as both densely and sparsely granulated. Bihormonal tumors presented only as HYPO and ISO. According to the Three Tissue Method, no HYPO was diagnosed with sparse granulation. Discussion We demonstrated discrepancies between SI assessment methods. Visual Method predicted the outcome of preoperative treatment with SSA. Clinically, ISO behaved similarly to HYPER. Further studies are needed to unify the SI assessment and improve its clinical applicability in acromegaly.